2019
DOI: 10.1111/nph.16223
|View full text |Cite
|
Sign up to set email alerts
|

Plant root exudation under drought: implications for ecosystem functioning

Abstract: Summary Root exudates are a pathway for plant–microbial communication and play a key role in ecosystem response to environmental change. Here, we collate recent evidence that shows that plants of different growth strategies differ in their root exudation, that root exudates can select for beneficial soil microbial communities, and that drought affects the quantity and quality of root exudation. We use this evidence to argue for a central involvement of root exudates in plant and microbial response to drought a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
225
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(232 citation statements)
references
References 55 publications
6
225
0
1
Order By: Relevance
“…Furthermore, HR induced wetting can support microbial communities that sustain vigorous nutrient cycling in the otherwise dry soil layers. Facilitation mechanisms could include regulation of root exudation on microbial activities (Williams and de Vries, 2020). This hypothesis is consistent with the frequent occurrence of HR in deep-rooted shrubs of arid and semi-arid regions (Kizito et al, 2007;Bogie et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, HR induced wetting can support microbial communities that sustain vigorous nutrient cycling in the otherwise dry soil layers. Facilitation mechanisms could include regulation of root exudation on microbial activities (Williams and de Vries, 2020). This hypothesis is consistent with the frequent occurrence of HR in deep-rooted shrubs of arid and semi-arid regions (Kizito et al, 2007;Bogie et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Specifically, we show that species turnover, likely caused by enviro-climatological changes resulted in a reshuffling of plant and microbial communities, which then led to a significant rewiring of plant-microbial interactions. Our results suggest that increasing network specialization may have been driven by a shift in physiological and metabolic activity across one organisational level (Blazewicz et al 2020;Williams & de Vries 2020), which then cascaded to the other level. Our findings highlight that while spatial patterns of diversity across trophic levels are indeed key to understand network specialization as forwarded by Galiana et al (2019), and that the contribution of novel associations between species that are common and shared across the networks is most prevalent.…”
Section: Discussionmentioning
confidence: 79%
“…Root exudation is a temporally dynamic process that can promote or inhibit the growth of particular microbial taxa [38]. It has been shown that drought and rewetting can modify exudate composition [39][40][41], which in turn could alter the activity of microorganisms at the root-soil interface [42]. Drought can also affect the growth and architectural properties of roots [43], potentially reshaping microbiome composition [44,45].…”
Section: Discussionmentioning
confidence: 99%